MEMBANDINGKAN PEMILU DAN PERSELISIHAN HASIL PEMILU PRESIDEN DAN WAKIL PRESIDEN TAHUN 2004 DAN TAHUN 2009 - Fadjar, Abdul Mukthie (Jurnal Konstitusi, 2010)
The realization of the 2004 and 2009 elections of the President and Vice President may be compared in terms of the quality and quantity. Qualitatively, the two elections are characterized by various dishonety and violations, although the violations may not yet be called sistematic, massive and structured ones. In general the elections may be held peacefully and safely, with little political tensions. Quantitatively, the 2009 election improved in terms of the number of voters, level of women participation, votes of the elected candidates, and increase in the presidential threshold. There were, however, some disputes on the election results in either 2004 or 2009. And the Constitutional Court of Law administered the case not only based on the qualitative disputes or the numbers of votes as determined by the General Election Commission (KPU) but also on the qualitative natures concerning with the process.